Effects of Pay Disclosure on Satisfaction for Sales Managers: A Longitudinal Study - Futrell, Charles M. (Academy of Management Journal, 1978)
The article discusses a study which examined the effects of pay disclosure on job satisfaction for sales managers. The author points out prior studies on the relationship between an open pay policy and various facets of job satisfaction. The impact of the implementation of an open pay policy on the pay and promotion satisfaction of managers was found to increase job satisfaction. A chart is presented that list the post-test minus pretest managers' satisfaction means by groups and sales regions. It was also found that the differences in satisfaction between the experimental and control groups varied considerably.